Thermodynamic solubility modelling, solvent effect and preferential solvation of p-nitrobenzamide in aqueous co-solvent mixtures of dimethyl sulfoxide, ethanol, isopropanol and ethylene glycol. (September 2019) - Yuan, Yang; Farajtabar, Ali; Kong, Liming; Zhao, Hongkun
Graphical abstract: Highlights: p -Nitrobenzamide solubility in four co-solvent mixtures was determined and correlated. Preferential solvation of p -nitrobenzamide in four mixtures were derived by IKBI method. Solvent effect was studied based on solute–solvent and solvent–solvent interactions. Abstract: The equilibrium p -nitrobenzamide solubility in mixtures of dimethyl sulfoxide (DMSO, 1) + water (2), ethanol (1) + water (2), isopropanol (1) + water (2) and ethylene glycol (EG, 1) + water (2) was determined with a shake-flask method from (293.15 to 328.15) K under atmospheric pressure (101.1 kPa). At the same temperature and mass fraction of DMSO (ethanol, isopropanol or EG), the mole fraction solubility of p -nitrobenzamide was greater in (DMSO + water) than in ethanol (1) + water (2), isopropanol (1) + water (2) and ethylene glycol (EG, 1) + water (2) mixtures. X-Ray power diffraction analysis of solid phase showed no polymorphic transformation or solvate formation in experiments. The degree of relative importance of solute–solvent and solvent–solvent interactions on the solubility variation was evaluated by the linear solvation energy relationship analysis of solvent effect. The inverse Kirkwood–Buff integrals was used to study the preferential solvation based on thermodynamic solution properties. The parameters of preferential solvation for ethanol and isopropanol were positive in the ethanol (1) + water (2) and isopropanol (1) + water (2) mixtures in co-solvent-rich and intermediate composition, indicating that p- nitrobenzamide was solvated preferentially by the co-solvent. p- Nitrobenzamide acted mainly as a Lewis acid interacting with proton-acceptor functional groups of the co-solvents. Moreover, the drugs' solubility was represented mathematically via the Jouyban-Acree model attaining the average relative deviations smaller than 2.16%.